Sfera sacrum w Cronaca del Luogo Luciana Beria - Nowak, Weronika (Res Facta Nova, 2019)
One can point to numerous manifestations of the sphere of sacrum in Luciano Berio’s stage works. It is created in the works of the Italian artist through the use of Christian symbolism, or that associated with the Judeo-Christian tradition, as in the case of Cronaca del Luogo (1999). The sphere of sacrum in Berio’s last stage work is created through such means as intertextual references to the Holy Writ, rabbinic and apocryphal literature and, linked to the creation of specific locations of the action – the space of sacred place, the palace and a Jewish cemetery. Even the title of the work points to the link between the work and the sphere of sacrum, and between the sphere of sacrum and the symbolism of space. This article will present an interpretation of these „imagined worlds” linked to the sphere of sacrum, created by the relationship between words, sounds and images, on the boundary between the space of the „wall” of Salzburg’s Felsen-reitschule, where the work had its premiere, and the imagination of its creators and audiences.